Neuropharmacological effects of standardized aqueous stem bark extract of Parkia biglobossa in Wistar rats - Tijani Adeniyi Yahaya; Samuel Ehiabhi Okhale; Salawu Oluwakanyinsola Adeola (Mashhad University of Medical Sciences, 2014)
Objective: Parkia biglobossa stem bark decoction is a popular medicinal plant preparation used as calming agent for tensed patients in traditional medicine. The aim of this study was to evaluate the effects of aqueous stem bark extract of Parkia biglobossa (AEPB) and its active fraction AEPBF3 on anxiety, spontaneous alternation behavior, and locomotor activity. The open field apparatus was used to evaluate effects of AEPB and AEPBF3 on locomotion.The APBE and the  active fraction AEPBF3 were standardized using reverse phase high performance liquid chromatography to establish finger print to ascertain identity and stability of the extracts over time. Materials and Methods: The oral median lethal doses (LD50) of AEPB and AEPBF3 were evaluated using modified Lorke's method in rats. The  effect of APBE (50-200 mg/kg p.o.), APBEF3 (25 and 50 mg/kg p.o.), diazepam (2.5 mg/kg, i.p.), and 10 ml normal saline/kg on anxiety-like behavior, spontaneous alternation behavior, and locomotion activity were evaluated in rats on elevated plus maze (EPM), Zero-maze, Y-maze, and open field apparatus, respectively. The oral LD50 values of AEPB and AEPBF3 were estimated to be 5000 mg/kg and 3800 mg/kg body weight in rats, respectively. Results: AEPB and AEPBF3 significantly (F6, 41=2342, p